2011
DOI: 10.1111/j.1748-8583.2010.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing in diverse organisations

Abstract: It has been argued that both strengths and weaknesses of diversity in organisations stem from the different demographic, national, linguistic, social and cultural backgrounds of their members. However, few attempts have been made to link different types of diversity to knowledge sharing despite the fact that organisations which can make full use of their collective knowledge and expertise could be expected to be more efficient, effective and creative. Therefore, a survey was directed towards 16 diverse academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 87 publications
1
54
0
3
Order By: Relevance
“…Task interdependence and variety of team members provide the necessity and space for individuals to collaborate and engage in knowledge exchange. This finding is similar to other studies in some respects (e.g., Lauring and Selmer, 2012;Liu and DeFrank, 2013;Migdadi, 2009;Swart and Kinnie, 2003) although we found that the more heterogeneous the team composition and the less permanent the team tenure, the higher the propensity for knowledge sharing. However, our finding contradicts Al-Adaileh and Al-Atawi's (2011) study in a telecommunications organisation in Saudi Arabia where they found that teamwork and collaboration did not necessarily promote knowledge sharing.…”
Section: Factors Affecting Knowledge Sharing Attitudesupporting
confidence: 82%
See 2 more Smart Citations
“…Task interdependence and variety of team members provide the necessity and space for individuals to collaborate and engage in knowledge exchange. This finding is similar to other studies in some respects (e.g., Lauring and Selmer, 2012;Liu and DeFrank, 2013;Migdadi, 2009;Swart and Kinnie, 2003) although we found that the more heterogeneous the team composition and the less permanent the team tenure, the higher the propensity for knowledge sharing. However, our finding contradicts Al-Adaileh and Al-Atawi's (2011) study in a telecommunications organisation in Saudi Arabia where they found that teamwork and collaboration did not necessarily promote knowledge sharing.…”
Section: Factors Affecting Knowledge Sharing Attitudesupporting
confidence: 82%
“…By positive attitude, we refer to the value that one places on knowledge and the sharing of it to enlarge the knowledge base (Swart and Kinnie, 2003). In a similar vein, we define positive behaviour as taking appropriate action such as engaging in formal and informal dialogue through feedback and questioning to challenge assumptions and offering new information that could help change the way others think and act (Lauring and Selmer, 2012).…”
Section: A Conceptual Framework Of Knowledge Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Malaysian study revealed that reciprocal relationships, sense of self-worth and subjective norm influenced staff attitudes towards knowledge sharing (Chong, Yuen and Gan 2014;Ramayah, Yeap and Ignatius 2013;Sohail and Daud, 2009). In the light of the Danish study, knowledge sharing had more positive associations with diversity related to cultural and linguistic internationalization, than demographic, such as age or gender (Lauring and Selmer 2012). According to Spanish studies, factors such as personal and professional profile, institutional variables and social networks had a very positive influence on knowledge sharing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…King et al (2007) concluded that differences between cultural backgrounds impact upon knowledge interplay and vice versa. Lauring and Selmer (2012) conducted a study of 16 diverse academic departments in Denmark within three large universities, and reported that there are positive impacts on sharing knowledge as a result of cultural and linguistic similarity. In addition the results of their study indicated that there are negative impacts with regards to differences in personal characteristics such as age and gender.…”
Section: Cultural Barriersmentioning
confidence: 99%